Land Degradation and Economic Development in Algeria - Mahcane, Zoubida; Abdellah, Mayou; Zergoune, Mohamed; Lacheheb, Miloud (International Journal of Energy Economics and Policy, 2018)
This study examines the relationship between land degradation and economic development in Algeria using the autoregressive distributed lag (ARDL) co-integration framework, and examine the existence of environmental Kuznets curve. The results based on the bound testing process endorse a long-run relationship between land degradation and economic development. Data were obtained from the FAO and World Bank Development Indicators for the period of 1970 to 2011. Importantly, our results reveal that land degradation insignificantly related to economic development, also, no evidence found for EKC hypothesis. Therefore, there is a dire need for technology improvement which may reduce the pressure on agriculture land demand and halt desertification. Keywords: Land degradation; Economic development; EKC; ARDL JEL Classifications: Q56, Q01, O11 DOI: https://doi.org/10.32479/ijeep.6947